1993
DOI: 10.1038/bjc.1993.283
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by verapamil of hepatocarcinogenesis induced by N-nitrosomorpholine in Sprague-Dawley rats

Abstract: Summary The effect of verapamil on hepatocarcinogenesis induced by N-nitrosomorpholine (NNM) was investigated in male Sprague-Dawley rats. Rats were given drinking water containing NNM for 8 weeks and received i.p. injections of verapamil or vehicle every other day for 16 weeks from the start of the experiment.Pre-neoplastic and neoplastic lesions staining positive for y-glutamyl transpeptidase (GGT) or the placental type of glutathione-S-transferase (GST-P) were examined histochemically at week 16. Prolonged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…However, in-vivo studies and animal models have shown inconsistent relationships between calcium channel blocking drugs and apoptosis; treatment with the drugs promotes apoptosis in some cancerous and noncancerous cell types and reduces apoptosis in others [ 23 29 ]. In fact, calcium channel blocking drugs appear to have antitumorigenic properties in some situations [ 30 33 ]. This lack of convincing biological evidence is consistent with the observed lack of association between calcium channel blocker use and breast cancer risk in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, in-vivo studies and animal models have shown inconsistent relationships between calcium channel blocking drugs and apoptosis; treatment with the drugs promotes apoptosis in some cancerous and noncancerous cell types and reduces apoptosis in others [ 23 29 ]. In fact, calcium channel blocking drugs appear to have antitumorigenic properties in some situations [ 30 33 ]. This lack of convincing biological evidence is consistent with the observed lack of association between calcium channel blocker use and breast cancer risk in this study.…”
Section: Discussionmentioning
confidence: 99%
“…S-(-)-VER is 10-20 times more potent than R-(+)-VER in slowing the cardiac A-V conduction velocity in humans, dogs and rabbits (Lankford and Bai, 1995;Mateus et al, 2007). Although R-(+)-VER has been shown to have lower antiarrhythmic potency, studies have found that this enantiomer has anti-tumor activity (Uehara et al, 1993;Warmann et al, 2002).…”
Section: Ver Is a Chiral Drug That Is Administered As A Racemic Mixtumentioning
confidence: 99%
“…20 -26 Moreover, CCBs have been shown to inhibit cell growth and metastasis in various models of neoplasia, including breast carcinoma. [27][28][29][30][31][32][33][34] The carcinogenic potential of CCBs has also been rigorously evaluated in whole animals with fully integrated systems. These animal genotoxicity studies have demonstrated unequivocally that there is not a link between CCB use and tumor development in animals, even at highly elevated drug concentrations administered over an extended period of time.…”
mentioning
confidence: 99%